DDAB-assisted synthesis of iodine-rich CsPbI3 perovskite nanocrystals with improved stability in multiple environments. Issue 7 (17th January 2020) - Huang, Yihui; Luan, Weiling; Liu, Mengke; Turyanska, Lyudmila
Abstract : Optimized method for synthesis of CsPbI3 NCs using dodecyldimethylammonium bromide as capping molecules can achieve enhanced stability. Abstract : All-inorganic cesium lead halide perovskite (CsPbX3, X = Cl, Br, I) nanocrystals (NCs) have attracted considerable attention due to their tunable optical properties and high optical quantum yield. However, their stability in various environments, such as different solvents, high temperature and UV light, remains to be addressed to enable their exploitation in devices. Here, we report on the synthesis of all inorganic CsPbI3 perovskite nanocrystals capped with didodecyldimethylammonium bromide (DDAB). Monodispersed DDAB-capped CsPbI3 NCs have enhanced stability with respect to their morphological and optical properties compared to conventional oleic acid (OA)/oleylamine (OLA) capped nanocrystals. The DDAB-CsPbI3 NCs retain an optical quantum yield >80% for at least 60 days. The enhanced stability is explained by the binding of branched DDAB ligands to the NC surface, leading to the formation of a halogen-rich surface, as confirmed by X-ray photoelectron spectroscopy, with an iodine to lead atomic ratio of I : Pb = 4 : 1. These perovskites were used in light-emitting diodes (LEDs) and have a maximum external quantum efficiency (EQE) of 1.25% and a luminance of 468 cd m −2, and demonstrated improved operational performance. The enhanced stability of DDAB-CsPbI3 in the environments relevant for device processing and operation is relevant for their exploitation in optoelectronics.